Bob's best ever friend - Bartram, Simon (Somerville, Mass. : Templar Books, 2009)
Bob, the man on the moon, is a bit lonely so decides to start looking for a best friend to keep him company, but his search is not going well until he spies a furry tail sticking out of crater 204.
Kirkus Review.
2.9
K-3
Keywords: Astronauts -- Juvenile fiction; Friendship -- Juvenile fiction; Life on other planets -- Juvenile fiction; Astronauts -- Fiction; Friendship -- Juvenile fiction; Life on other planets -- Fiction; Astronauts -- Fiction; Friendship -- Fiction; Life on other planets -- Fiction